2008
DOI: 10.1111/j.1939-1676.2008.0161.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NT‐Pro BNP and CT‐ANP as Markers of Concentric Hypertrophy in Dogs with a Model of Compensated Aortic Stenosis

Abstract: Background: Serum C-terminal atrial natriuretic peptide (CT-ANP) and N-terminal pro B-type natriuretic peptide (NT-pro BNP) concentrations have not been measured serially in dogs with chronic pressure overload of the heart. Hypothesis: We investigated whether serial evaluation of CT-ANP and NT-pro BNP concentrations is a useful guide to the risk of cardiac remodeling in dogs with a model of aortic stenosis.Animals: Six male Beagles. Methods: After anesthesia, the aorta was constricted with a polyester band and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…NT-proBNP acted as a predictive biomarker of heart drug-induced liability as has been reported previously elsewhere (Panou et al 2006;Hori et al 2008). Moreover, these results provide evidence that NT-proBNP represents an excellent translational tool in assessing potential cardiotoxicity in preclinical studies during drug development.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…NT-proBNP acted as a predictive biomarker of heart drug-induced liability as has been reported previously elsewhere (Panou et al 2006;Hori et al 2008). Moreover, these results provide evidence that NT-proBNP represents an excellent translational tool in assessing potential cardiotoxicity in preclinical studies during drug development.…”
Section: Discussionsupporting
confidence: 69%
“…As for humans, recent studies have shown that assessment of NT-proBNP concentration may be useful in identifying cardiac disease in dogs and grading disease severity Takemura et al 2009;Serres et al 2009;Piantedosi et al 2009;Moonarmart et al 2010). In a recent paper, the main role of NT-proBNP determination for the identification of early stage ventricular remodeling, secondary to aortic stenosis in dogs, was shown (Hori et al 2008). Authors were able to demonstrate a statistically significant correlation between NT-proBNP concentrations and left ventricular end-diastolic pressure and end-diastolic intraventricular septum thickness.…”
Section: Introductionmentioning
confidence: 94%
“…Previous reports indicated reference values for the serum NT-proBNP concentration in normal dogs were 324 ± 119 pmol/L (mean value ± SD) [16] and 290 pmol/L (mean value) [22]. In addition, the NT-proBNP assay had adequate sensitivity and specificity for diagnosis of heart failure.…”
Section: Discussionmentioning
confidence: 94%
“…For example, in a pressure-overload model of aortic banding in 6 male Beagles, it was shown that NT-proBNP better correlated with left ventricular end diastolic pressures when compared to NT-proANP. 108 In addition, recent publications demonstrated that the diagnostic and prognostic value of NT-proBNP in cats and dogs was superior to NT-proANP. 109,110 In contrast to humans, 111 BNP and NT-proBNP concentrations in animals seem to be less associated with age or gender, while the associations with body weight and renal impairment have been found.…”
Section: Natriuretic Peptide Testing In Veterinary Medicinementioning
confidence: 98%